(untitled) (Innovative professional education, 2024)
The article discusses the issues of improving the quality of vocational education and training as an important prerequisite for achieving sustainable development of society, a tool for effective management of the competitiveness of the country’s labour potential. A significant role in ensuring the quality of training of future specialists belongs to teachers with a high level of professional competence. The article presents the results of a pedagogical study of the development of professional competence of teachers of specialised disciplines of agricultural colleges.